Pay for performance associated with increased volume of medication reviews but not with less inappropriate use of medications among the elderly – an observational study. (3rd July 2017) - Ödesjö, H.; Anell, A.; Boman, A.; Fastbom, J.; Franzén, S.; Thorn, J.; Björck, S.
Abstract: Objective: A pay for performance programme was introduced in 2009 by a Swedish county with 1.6 million inhabitants. A process measure with payment linked to coding for medication reviews among the elderly was adopted. We assessed the association with inappropriate medication for five years after baseline. Design and setting: Observational study that compared medication for elderly patients enrolled at primary care units that coded for a high or low volume of medication reviews. Patients: 144, 222 individuals at 196 primary care centres, age 75 or older. Main outcome measures: Percentage of patients receiving inappropriate drugs or polypharmacy during five years at primary care units with various levels of reported medication reviews. Results: The proportion of patients with a registered medication review had increased from 3.2% to 44.1% after five years. The high-coding units performed better for most indicators but had already done so at baseline. Primary care units with the lowest payment for coding for medication reviews improved just as well in terms of inappropriate drugs as units with the highest payment – from 13.0 to 8.5%, compared to 11.6 to 7.4% and from 13.6 to 7.2% vs 11.8 to 6.5% for polypharmacy. Conclusions: Payment linked to coding for medication reviews was associated with an increase in the percentage of patients for whom a medication review had been registered. However, the impact of payment on quality improvement is uncertain, given that units with the lowest payment for medication reviews improved equally well as units with the highest payment.